Design and Implementation of a Web-Based Digital Repository System in the Muamalah Study Program at UINSU Using the Waterfall Method - Diah Putri Kartikasari; Farhan, Muhammad (Ali Institute of Research and Publication, 2025)
Repository is a digital storage system that can store various kinds of data such as files, documents, and research results, often a repository is called a digital library by many people. Repository is used in various places, one of which is higher education, which can store student research results such as papers, theses, journals, thesis, and dissertations. Muamalah repository is addressed to the Muamalah Study Program, Faculty of Sharia and Law, State Islamic University of North Sumatra which still uses a manual library system so that it can cause problems in the process of searching, storing and managing documents that require a long time. So a digital library or digital repository is the right solution to deal with these problems. The waterfall software development method is used in this research because the process is structured and more organized so that it can facilitate research. The use of UML (Unified Modeling Language) as a design model and PHP (Hypertext Prepocessor) as a programming language makes this research easier to implement. The results of this study can help the muamalah study program in managing various data such as theses, journals, thesis, and so on